48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-1572
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Computations of Hypersonic Boundary-Layer over Surface Irregularities

Abstract: Surface irregularities such as protuberances inside a hypersonic boundary layer may lead to premature transition on the vehicle surface. Early transition in turn causes large localized surface heating that could damage the thermal protection system. Experimental measurements as well as numerical computations aimed at building a knowledge base for transition Reynolds numbers with respect to different protuberance sizes and locations have been actively pursued in recent years. This paper computationally investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
3
24
1
Order By: Relevance
“…Analogous streaks have been noted in recent computations modeling select flow conditions from the present experiment. 15,16 High amplitude stationary streaks of this type can have strong temperature gradients (see for example, Fig. 11 of Ref.…”
Section: A 10 Hz No Plif Flow Visualization 1 Interpretation Of No mentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous streaks have been noted in recent computations modeling select flow conditions from the present experiment. 15,16 High amplitude stationary streaks of this type can have strong temperature gradients (see for example, Fig. 11 of Ref.…”
Section: A 10 Hz No Plif Flow Visualization 1 Interpretation Of No mentioning
confidence: 99%
“…11 of Ref. 15) and, furthermore, can transport unseeded fluid towards the wall, adjacent to the seeded fluid. Both of these effects (temperature and NO density gradients) contribute to the strong contrast in the fluorescence intensity in the image.…”
Section: A 10 Hz No Plif Flow Visualization 1 Interpretation Of No mentioning
confidence: 99%
“…We note that the possibility of self-sustained unsteadiness in the immediate vicinity of the roughness element cannot be ruled out entirely. 5 However, the main focus herein is to compare the stability characteristics in the mean wake flow and, since the L2 norms of the residual levels had dropped to O(10 -11 ) or less when they leveled off, it was assumed that the wake flow computed via local time stepping would provide a meaningful basic state for the analysis of wake instabilities. Future computations are planned to verify this assumption as well as to confirm the accuracy of the IBM in the Mach 6 cases.…”
Section: Mean Wake Flowmentioning
confidence: 99%
“…The flow behind an isolated roughness element was further investigated by Chang et al, 5 who addressed the potential onset of spontaneous unsteadiness behind a roughness element of height that is close to the boundary layer thickness. It was shown that the wake flow spontaneously became unsteady at sufficiently large roughness heights, exhibiting a complex interplay between the unsteadiness in the separation region immediately upstream of the roughness element and the disturbance motion farther downstream within the wake.…”
Section: Introductionmentioning
confidence: 99%
“…The global HYTHIRM and the companion discrete BLT Flight Experiment measurements have fostered a diverse set of complementary work highlighting a variety of advancements in both experimental technique 27,28 and numerical modeling 29,[32][33] . In terms of CFD, turbulence models play a crucial role in the simulation of complex flows where separation, shock/boundary layer interaction, and flow reattachment are present.…”
Section: Comparison To Predictionmentioning
confidence: 99%